Pengaruh Penanaman Modal dalam Negeri dan Modal Asing Terhadap Investasi dan Penyerapan Tenaga Kerja di Provinsi Sumatra Utara - Rista Y.Lumban Gaol; Joko Suharianto (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This study aims to determine and analyze: (1).The effect of domestic investment) on the absorption of sectoral labor in Southeast Sulawesi Province. (2) The effect of foreign direct investment on sectoral employment in Southeast Sulawesi Province. The research method used is quantitative research. Collecting data using document study techniques. The data analysis technique used was statistical descriptive analysis, and multiple regression analysis of panel data. The results of the study conclude that: (1) Domestic Investment (PMDN) has a significant and positive effect on sectoral employment in Southeast Sulawesi Province. This means that an increase in domestic investment can increase the absorption of sectoral workers in Southeast Sulawesi Province. (2) Foreign Direct Investment (PMA) has a significant and positive effect on sectoral employment in Southeast Sulawesi Province. This means that an increase in investment from abroad can increase the absorption of sectoral labor in Southeast Sulawesi Province, but the increase is relatively small.